HAEMODYNAMIC RESPONSES TO TRACHEAL EXTUBATION OR LARYNGEAL MASK AIRWAY REMOVAL IN PATIENTS UNDERGOING SHORT SURGICAL PROCEDURES: A COMPARATIVE AND CLINICAL STUDY - PHAPHAGIRE, NIKITA BHAGWAT; UBALE, PRAVIN; B SYED, ANESA (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Aims and Objectives: The aim of the study was to evaluate and compare the hemodynamic responses after endotracheal tube (ET) extubation and laryngeal mask airway (LMA) removal in American Society of Anaesthesiologists (ASA) I and ASA II patients undergoing short surgical procedures. Methods: This was a randomized, comparative, observational, and clinical study conducted in a tertiary care medical college. The duration of study was 1 year. Hundred patients of ASA Grade I and II with age between 18 and 60 years, including both males and females posted for short surgeries under general anesthesia were selected for the study. Patients were divided into two groups (Depending on whether endotracheal intubation was done or LMA was used) of 50 patients each. Hemodynamic parameters (systolic blood pressure [SBP], diastolic blood pressure [DBP], mean arterial pressure [MAP], and heart rate [HR]) were recorded and compared before induction, during surgery and postoperatively at 1, 2, 5, and 10 min between both the groups. Results: There was no significant difference between these two groups regarding the demographic aspect of the patients such as age and gender. Furthermore, the parameters such as ASA grade and duration of surgery were comparable. The baseline hemodynamic parameters between the two groups were also similar and no significant difference was observed. The changes in hemodynamics (mean HR, SBP, DBP, and MAP) were more in Group E as compared to Group L and the difference was found to be statistically significant (p<0.05). Similarly respiratory events were more profound in Group E as compared to Group L and the difference was found to be statistically significant (p<0.05). Conclusion: LMA is a better choice for short surgical procedures as it provides more hemodynamic stability during removal as compared to ET extubation. LMA is also associated with less complications as compared to ET.